RETURN ON INVESTMENT DENGAN SISTEM DU PONT PADA PT BUSSAN AUTO FINANCE - Simbolon, Davrinus Pahotan (EKONOMIA, 2015)
This study aims to determine the decrease in return on investment with Du Pont system. Outlines the basic theory of Accounting, Financial Accounting, Financial Statements, Financial Statement Analysis Model Du Pont. The analysis tool used is the Return On Investment by Du Pont system, because it is a thorough analysis we can also determine the extent to which the effectiveness of PT Bussan Auto Finance in turning capital. PT Bussan Auto Finance (BAF) is Yamaha's official financing company, this company provides a variety of financial services products such as leasing, factoring, and consumer financing. PT Bussan Auto Finance would have to pay attention to things that affect their growth. For the details of the data used is the financial statement balance sheet and income statement. Based on the analysis of return on investment that has been made during the period 2006 to 2012 found a decreased Return On Investment. This decrease was seen in the results of the comparison from year to year. The decrease was due to a lack of revenue annually. Then it can be seen as a whole that results Return On Investment PT Bussan Auto Finance fluctuate.